The GLEAM 200-MHz local radio luminosity function for AGN and star-forming galaxies. (6th September 2021) - Franzen, T. M. O.; Seymour, N.; Sadler, E. M.; Mauch, T.; White, S. V.; Jackson, C. A.; Chhetri, R.; Quici, B.; Bell, M. E.; Callingham, J. R.; Dwarakanath, K. S.; For, B.; et al.
Abstract: The GaLactic and Extragalactic All-sky Murchison Widefield Array (GLEAM) is a radio continuum survey at 76–227 MHz of the entire southern sky (Declination <\!+30^° ) with an angular resolution of ≈2 arcmin. In this paper, we combine GLEAM data with optical spectroscopy from the 6dF Galaxy Survey to construct a sample of 1 590 local (median z ≈ 0.064 ) radio sources with S_200 MHz > 55 mJy across an area of ≈16 700 deg^2 . From the optical spectra, we identify the dominant physical process responsible for the radio emission from each galaxy: 73% are fuelled by an active galactic nucleus (AGN) and 27% by star formation. We present the local radio luminosity function for AGN and star-forming (SF) galaxies at 200 MHz and characterise the typical radio spectra of these two populations between 76 MHz and 1 GHz. For the AGN, the median spectral index between 200 MHz and 1 GHz, α_high, is -0.600 ± 0.010 (where S ν^α ) and the median spectral index within the GLEAM band, α_low, is -0.704 ± 0.011 . For the SF galaxies, the median value of α_high is -0.650 ± 0.010 and the median value of α_low is -0.596 ± 0.015 . Among the AGN population, flat-spectrum sources are more common at lower radio luminosity, suggesting the existence of a significant population of weak radio AGN that remain core-dominated even at low frequencies. However, around 4% of local radio AGN have ultra-steep radio spectra at low frequencies ( α_low < -1.2 ). These ultra-steep-spectrum sources span a wide range in radio luminosity, and further work is needed to clarify their nature.